Exploring the Intersections of Blue, Green, and Grey Economies in Nigeria: Opportunities, Challenges, and Strategic Pathways for Sustainable Development - Jacob, Augustine; Umoh, Okon (Journal of Sustainable Economics, 2025)
This review paper explores the integration of Blue, Green, and Grey economies as viable pathways for sustainable economic development in Nigeria. By examining the principles, current status, challenges, and opportunities of these economic models, the study highlights their potential in diversifying Nigeria's economy, enhancing environmental sustainability, and promoting social inclusion. The Blue Economy focuses on harnessing Nigeria’s vast coastal and marine resources for sustainable fisheries, aquaculture, and maritime activities. The Green Economy emphasizes eco-friendly practices, renewable energy, sustainable agriculture, and land management as means to address climate change and improve food security. Meanwhile, the Grey Economy, predominantly informal, presents opportunities for sustainable urban development, particularly in waste management, recycling, and construction sectors. The study identifies significant challenges, including policy gaps, inadequate infrastructure, limited access to financing, and the need for a more robust regulatory framework. It emphasizes the necessity of an integrated policy approach that aligns with Nigeria’s Vision 2050 and the Sustainable Development Goals (SDGs). Strategic recommendations include fostering public-private partnerships, investing in capacity building, and leveraging innovative financing mechanisms to support sustainability projects. This review concludes that a comprehensive approach to integrating Blue, Green, and Grey economies can enhance Nigeria’s economic resilience, reduce environmental degradation, and promote inclusive growth. The findings serve as a blueprint for policymakers, stakeholders, and researchers interested in advancing sustainable development in Nigeria.